A copper-chromium-scandium alloy and preparation method thereof

By using Sc to replace Zr in copper-chromium alloy, combined with deep cold rolling and multi-step process processing, the component control problem caused by zirconium is solved, and the composition stability and excellent mechanical and electrical properties of copper-chromium scandium alloy are achieved. , suitable for high-performance applications.

CN116426789BActive Publication Date: 2025-02-18HENAN UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310481931.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2025-02-18
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

The existing chromium copper alloys are difficult to control the alloy composition due to the use of zirconium elements and cannot achieve mass production applications.

Method used

Using Sc instead of the burn-in element Zr to prepare copper-chromium scandium alloy, it can be processed through deep cold rolling technology and multi-step process (such as homogenization treatment, forging, solid solution treatment, equal diameter angle extrusion and aging treatment) to obtain excellent results. mechanical and electrical properties.

Benefits of technology

It has achieved the composition stability of copper-chromium scandium alloy, and has excellent mechanical properties, electrical conductivity and thermal conductivity. It is suitable for high-speed railway contact lines, large-scale integrated circuit lead frames and other fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a copper-chromium-scandium alloy and a preparation method thereof, and belongs to the technical field of copper alloy materials. The copper-chromium-scandium alloy of the present invention uses Sc to replace the easily burnt element Zr, thereby obtaining a copper alloy having excellent mechanical properties, electrical and thermal conductivity, and high temperature softening resistance. The electrical conductivity of the copper-chromium-scandium alloy of the present invention is ≥82%IACS, and the thermal conductivity is ≥392W·(m·K). ‑1 , room temperature tensile strength ≥470MPa, elongation ≥9%, which can meet the product needs of high-speed railway contact lines, large-scale integrated circuit lead frames, high-pulse electromagnetic coils, nuclear fusion energy power generation and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a copper-chromium-scandium alloy and a preparation method thereof, belonging to the technical field of copper alloy materials. Background Art

[0002] As a typical aging precipitation strengthened copper alloy, chromium copper-based alloy has good high strength and high conductivity, and can be used in large-scale integrated circuit lead frames, high-speed railway contact wires, high-end connectors and other fields. It is also an important candidate material for heat sink components of nuclear fusion reactors. In order to adapt to the high temperature working environment inside the nuclear reactor, the alloy is required to have excellent mechanical properties, high heat resistance and high thermal conductivity.

[0003] At present, chromium-zirconium-copper alloy is a typical chromium-copper alloy with excellent comprehensive properties. For example, Chinese patent document CN 109385555A discloses a copper-chromium-zirconium alloy, which is made of the following raw materials: 0.2-1.2% chromium, 0.05-0.2% zirconium, 0.06-0.10% magnesium, 0.05-0.5% scandium, and the balance is copper. The copper-chromium-zirconium alloy disclosed in the document has high tensile strength, high electrical conductivity and high elongation, and has high high-temperature tensile strength and excellent comprehensive properties. However, when smelted under atmospheric conditions, zirconium (Zr) is easy to burn and easily react with the substrate, resulting in the difficulty in controlling the composition of the chromium-zirconium-copper alloy and the inability to achieve mass production and application. In addition, magnesium is an active metal, and the composition is not easy to control when added.

[0004] Therefore, developing chromium-copper alloys whose alloy composition is relatively easy to control and which have excellent mechanical properties, high temperature resistance and thermal conductivity can provide reserve materials for the field of nuclear fusion power generation, thereby promoting the development of nuclear fusion energy, reducing dependence on fossil energy, and is of great significance to environmental protection. Summary of the invention

[0005] The object of the present invention is to provide a copper-chromium-scandium alloy, which can solve the problem that the alloy composition of the current chromium-copper alloy is difficult to control due to the use of zirconium element, and mass production and application cannot be achieved.

[0006] Another object of the present invention is to provide a method for preparing the copper-chromium-scandium alloy.

[0007] In order to achieve the above objectives, the technical solution adopted by the copper-chromium-scandium alloy of the present invention is:

[0008] A copper-chromium-scandium alloy is composed of the following elements in percentage by mass: 0.16-0.2% chromium, 0.08-0.15% scandium, and the remainder copper and unavoidable impurity elements.

[0009] The copper-chromium-scandium alloy of the present invention uses Sc to replace the easily burnt element Zr to obtain a copper alloy with excellent mechanical properties, electrical and thermal conductivity and high temperature softening resistance. The electrical conductivity of the copper-chromium-scandium alloy of the present invention is ≥82% IACS, and the thermal conductivity is ≥392W·(m·K) -1 , room temperature tensile strength ≥470MPa, elongation ≥9%, which can meet the product needs of high-speed railway contact lines, large-scale integrated circuit lead frames, high-pulse electromagnetic coils, nuclear fusion energy power generation and other fields.

[0010] Experiments show that when Sc is a typical light rare earth element, it is added to pure copper alone and combined with deep cold rolling technology to prepare a Cu-Sc binary alloy with a yield strength of 696 MPa and a conductivity of 63% IACS.

[0011] Preferably, in the copper-chromium-scandium alloy, the mass percentage of the chromium element is 0.18-0.2%, and the mass percentage of the scandium element is 0.11-0.15%.

[0012] Preferably, the impurity elements are selected from one or any combination of aluminum, silicon, iron and tin; and in the copper-chromium-scandium alloy, the mass percentage of the impurity elements is not greater than 0.05%.

[0013] The technical solution adopted by the preparation method of the copper-chromium-scandium alloy of the present invention is:

[0014] A method for preparing a copper-chromium-scandium alloy comprises the following steps: smelting copper, a copper-chromium master alloy and scandium, then casting to obtain an ingot, and then sequentially subjecting the ingot to homogenization treatment, forging, solution treatment, equal-diameter angular extrusion and aging treatment to obtain the copper-chromium-scandium alloy.

[0015] The preparation method of the copper-chromium-scandium alloy of the present invention is simple to operate. The composition fluctuation rate of the prepared copper-chromium-scandium alloy is within ±0.02%, and the alloy has good tensile strength, elongation, high electrical conductivity and thermal conductivity, and is suitable for the fields of continuous casting crystallizers, high-end connectors and connectors. The homogenization treatment is to eliminate the uneven composition generated during the casting process; the hot forging is to eliminate the defects generated during the casting process and refine the grains; the solid solution treatment allows the solute to be fully dissolved in the copper matrix; the equal-diameter angular extrusion is to obtain finer micron-level grains to strengthen the matrix, and the aging treatment is to promote the precipitation of Cr from the supersaturated solid solution to form a dispersed nano-level precipitation phase, further strengthen the matrix, and give full play to the synergistic improvement effect of the equal-diameter angular extrusion + aging treatment on the mechanical properties and electrical properties of the copper-chromium-scandium alloy, and finally obtain a copper-chromium-scandium alloy with excellent comprehensive performance.

[0016] Preferably, the purity of the copper is not less than 99.95%. Further preferably, the purity of the copper is not less than 99.99%. Preferably, the copper is electrolytic copper.

[0017] In order to ensure that scandium is better smelted and evenly distributed in the ingot, preferably, in the method for preparing the copper-chromium-scandium alloy, the scandium is used in the form of scandium powder.

[0018] Preferably, the copper-chromium master alloy is a Cu-25Cr master alloy. Since the melting point of chromium is high (1907°C) and it is not easy to melt, it is difficult to reach its melting temperature during the smelting process. The use of a master alloy (Cu-25Cr master alloy) facilitates its melting into the matrix during the smelting process, which is conducive to more precise control of the composition and obtaining a melt with uniform distribution of the alloy element chromium. In addition, the use of a master alloy can also shorten the smelting time, reduce melting loss and avoid overheating of the melt.

[0019] Preferably, the purity of scandium is not less than 99.8%.

[0020] Preferably, the smelting temperature is 1150-1250° C. Preferably, the smelting time is 30-50 min.

[0021] Preferably, the smelting is carried out in a slightly oxidizing atmosphere. Preferably, the slightly oxidizing atmosphere is to use charcoal to cover the molten liquid surface during the heating and melting process of the raw materials, and to use graphite rods for stirring and slagging during the smelting process. Since graphite rods are resistant to high temperatures, and stirring with graphite rods can avoid the introduction of impurities.

[0022] Preferably, the casting temperature is 1200-1300° C. If the casting temperature is too high, it will cause serious element ablation and make it difficult to control the composition of the copper-chromium-scandium alloy; if the casting temperature is too low, it will cause uneven distribution of solute atoms and poor melt fluidity during casting.

[0023] Preferably, the homogenization treatment is to keep the ingot at 850°C to 900°C. Preferably, the homogenization treatment time is not less than 3 hours. For example, the homogenization treatment time is 3 hours. If the homogenization treatment temperature is too high, it will cause matrix ablation. In addition, in the subsequent forging cooling process, it will also cause the grains to continue to grow, thereby reducing its mechanical properties. If the homogenization treatment temperature is too low, the plasticity of the ingot will be reduced, the deformation resistance will increase sharply, and a large residual stress will be generated inside.

[0024] Preferably, the forging is to forge the ingot after homogenization treatment at a temperature of 850°C to 900°C in the air. Preferably, the deformation of the forging is 60% to 65%. Preferably, the forging is completed within 2 minutes. If the forging temperature is too high, it will cause matrix ablation. In addition, during the cooling process, it will also cause the grains to continue to grow, thereby reducing its mechanical properties. If the forging temperature is too low, work hardening will occur inside the forging blank, reducing plasticity, sharply increasing deformation resistance, and generating large residual stress inside. If the forging deformation is too small, the forging will not meet the performance requirements. If the forging deformation is too large, on the one hand, the effect of continuing to refine the grains is limited, and on the other hand, it will cause anisotropy.

[0025] Preferably, the temperature of the solution treatment is 890-970°C and the time is 0.5-2h. If the temperature of the solution treatment is too high, the matrix will be overburned and the structure will be coarse; if the temperature of the solution treatment is too low, the solution time will be prolonged, the solute elements will not be fully dissolved, and excessive energy consumption will be caused; if the solution treatment time is too short, the solute distribution will be uneven; if the solution treatment time is too long, the grains will be coarse and unnecessary energy consumption will be caused.

[0026] Preferably, the solution treatment is performed in a protective gas. Preferably, the protective gas is nitrogen and / or argon.

[0027] Preferably, the solution treatment method comprises the following steps: heating the forged ingot to 890-970°C, keeping the temperature for 0.5-2h, and then cooling. Preferably, in the solution treatment method, the cooling is water cooling.

[0028] Preferably, the inner angle of the ECA extrusion channel is 90° to 110°, and the outer angle is 10° to 30°. For example, the inner angle of the ECA extrusion channel is 90°, and the outer angle is 20°.

[0029] Preferably, the extrusion speed of the equal channel angular extrusion is 2 to 10 mm / s.

[0030] Preferably, the equal-channel angular pressing has no less than 4 extrusion passes. Too few equal-channel angular pressing passes may result in uneven grain refinement and poor effect.

[0031] Preferably, the equal-channel angular extrusion is performed at room temperature. Compared with equal-channel angular extrusion at high temperature, equal-channel angular extrusion at room temperature not only saves energy, but also helps to reduce dynamic recovery and recrystallization of grains.

[0032] Preferably, the temperature of the aging treatment is 450-510°C, and the time is 0.5-10h. If the temperature of the aging treatment is too high, the precipitation phase will precipitate and grow rapidly, the fine grains will recover and recrystallize, and the mechanical properties will be reduced. If the temperature of the aging treatment is too low, the thermodynamic driving force for the precipitation phase will be small, which is not conducive to the precipitation of solute atoms from the supersaturated solid solution, and a longer aging time will be required; if the aging treatment time is too short, the solute atoms will not be completely precipitated from the supersaturated solid solution, which is not conducive to the improvement of mechanical and electrical properties. If the aging treatment time is too long, the precipitation phase will coarsen and grow, resulting in a reduction in mechanical properties.

[0033] Preferably, the aging treatment is carried out in a protective gas. Preferably, the protective gas used in the aging treatment is nitrogen and / or argon.

[0034] Preferably, the aging treatment method comprises the following steps: heating the ingot after equal-channel angular extrusion to 450-510°C, keeping the temperature for 0.5-10 hours, and then cooling. Preferably, in the aging treatment method, the cooling is air cooling. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0036] 1. The specific embodiments of the copper-chromium-scandium alloy of the present invention are as follows:

[0037] Example 1

[0038] The copper-chromium-scandium alloy of this embodiment is composed of the following elements in percentage by mass: 0.16% chromium, 0.08% scandium, and the remainder copper and unavoidable impurity elements; the mass percentage of the impurity elements is no more than 0.05%.

[0039] Example 2

[0040] The copper-chromium-scandium alloy of this embodiment is composed of the following elements in percentage by mass: 0.18% chromium, 0.11% scandium, and the remainder copper and unavoidable impurity elements; the mass percentage of the impurity elements is no more than 0.05%.

[0041] Example 3

[0042] The copper-chromium-scandium alloy of this embodiment is composed of the following elements in percentage by mass: 0.2% chromium, 0.15% scandium, and the remainder copper and unavoidable impurity elements; the mass percentage of the impurity elements is no more than 0.05%.

[0043] Comparative Example 1

[0044] The copper-chromium-scandium alloy of this comparative example is different from the copper-chromium-scandium alloy of Example 1 only in that the mass fraction of chromium in the copper-chromium-scandium alloy of this comparative example is 0.14%.

[0045] Comparative Example 2

[0046] The copper-chromium-scandium alloy of this comparative example is different from the copper-chromium-scandium alloy of Example 1 only in that the mass fraction of the scandium element in the copper-chromium-scandium alloy of this comparative example is 0.06%.

[0047] Comparative Example 3

[0048] The copper-chromium-scandium alloy of this comparative example is different from the copper-chromium-scandium alloy of Example 3 only in that the mass fraction of chromium in the copper-chromium-scandium alloy of this comparative example is 0.22%.

[0049] Comparative Example 4

[0050] The copper-chromium-scandium alloy of this comparative example is different from the copper-chromium-scandium alloy of Example 3 only in that the mass fraction of the scandium element in the copper-chromium-scandium alloy of this comparative example is 0.18%.

[0051] Comparative Example 5

[0052] The copper-based alloy of this comparative example is different from the copper-chromium-scandium alloy of Example 3 only in that the scandium element is replaced by the Y element in the copper-based alloy of this comparative example.

[0053] Comparative Example 6

[0054] The copper-based alloy of this comparative example is different from the copper-chromium-scandium alloy of Example 3 only in that in the copper-based alloy of this comparative example, the scandium element is replaced by the Tm element.

[0055] The preparation method of the copper-based alloy of Comparative Example 1-2 was prepared by referring to the preparation method of the copper-based alloy of Example 1.

[0056] The preparation methods of the copper-based alloys of Comparative Examples 3-6 are prepared by referring to the preparation method of the copper-based alloy of Example 3. The copper-based alloys of Comparative Examples 5-6 are prepared using Y powder and Tm powder with a purity greater than 99.9%, and the particle size of the Y powder and Tm powder is the same as the particle size of the pure scandium powder used in the preparation method of the copper-based alloy of Example 3.

[0057] 2. The specific embodiment of the preparation method of the copper-chromium-scandium alloy of the present invention is as follows:

[0058] Example 4

[0059] The preparation method of the copper-chromium-scandium alloy of this embodiment is the preparation method of the copper-chromium-scandium alloy of embodiment 1, and specifically comprises the following steps:

[0060] (1) Cutting, drying and surface degreasing the electrolytic copper plate and Cu-25Cr master alloy with a purity of ≥99.99%, and then adding the treated electrolytic copper plate, Cu-25Cr master alloy and pure scandium powder (Sc≥99.8%) into a smelting furnace according to a proportion for melting, the melting temperature is 1200° C., the melting time is 40 min, and during the heating and melting process, the molten liquid surface is ensured to be completely covered by charcoal, and most of the air is isolated by the charcoal covering layer to achieve the melting process in a slightly oxidizing atmosphere. During the melting process, a graphite stirring rod is used for stirring, and a slag removal rod is used for slag removal; after the surface of the molten liquid becomes mirror-like, the molten liquid is allowed to stand for 1 min, and then the molten liquid is heated to 1250° C., and the molten liquid with a temperature of 1250° C. is poured into a metal casting mold, and after cooling to room temperature, the molten liquid is taken out to obtain an ingot;

[0061] (2) The ingot is machined on a common lathe with a circumference and bottom end surface machining amount of 2 mm on a single side and a end surface machining amount of 2 mm; then, the ingot after circumference and bottom end surface machining is placed on a sawing machine for sawing, and the riser on the top of the ingot is removed, and the length of the sawing off is 1 / 5 of the total height of the ingot;

[0062] (3) placing the ingot after the treatment in step (2) in a box furnace at 850° C. for 3 h to perform homogenization treatment, then taking the ingot after the homogenization treatment out of the box furnace for hot forging, the forging is completed within 2 min, and the forging deformation is 62% (the forging deformation is calculated based on the cross-sectional ratio before and after forging);

[0063] Then the forged ingot is placed in a gas-protected tubular furnace at a temperature of 890°C (the gas in the gas-protected tubular furnace is a mixture of nitrogen and argon with a volume ratio of 1:1) and kept warm for 0.5h, then taken out and quickly placed in running tap water for cooling to complete the solution treatment. The total time of taking the ingot out of the gas-protected tubular furnace and placing it in running tap water is controlled to be no more than 5s;

[0064] Then, the ingot after the solution treatment was subjected to equal-channel angular extrusion. The process conditions of the equal-channel angular extrusion were as follows: Bc path was adopted, the extrusion speed was 6 mm / s, the number of extrusion passes was 4, the extrusion temperature was room temperature, the inner angle of the equal-channel angular extrusion channel was 90°, and the outer angle was 20°;

[0065] The ingot after equal-diameter angular extrusion is then placed in a gas-shielded tubular furnace at a temperature of 450°C (the gas in the gas-shielded tubular furnace is a mixture of nitrogen and argon in a volume ratio of 1:1) and kept warm for 0.5 hours. It is then taken out and cooled in the air to room temperature to complete the aging treatment to obtain a copper-chromium-scandium alloy.

[0066] Example 5

[0067] The preparation method of the copper-chromium-scandium alloy of this embodiment is the preparation method of the copper-chromium-scandium alloy of embodiment 2, and specifically comprises the following steps:

[0068] (1) Cutting, drying and surface degreasing the electrolytic copper plate and Cu-25Cr master alloy with a purity of ≥99.99%, and then adding the treated electrolytic copper plate, Cu-25Cr master alloy and pure scandium powder (Sc≥99.8%) into a smelting furnace according to a proportion for melting, the melting temperature is 1250° C., the melting time is 50 min, during the heating and melting process, the molten liquid surface is ensured to be completely covered by charcoal, and most of the air is isolated by the charcoal covering layer to achieve the melting process in a slightly oxidizing atmosphere, stirring with a graphite stirring rod and slag removal with a slag removal rod during the melting process; after the molten liquid surface becomes mirror-like, standing for 1 min, then heating the molten liquid to 1300° C., and pouring the molten liquid at a temperature of 1300° C. into a metal casting mold, cooling to room temperature, and taking it out to obtain an ingot;

[0069] (2) machining the circumference and the bottom end face of the ingot on a CNC lathe, with the circumference machining amount being 2 mm on a single side and the end face machining amount being 2 mm; then, placing the ingot after the circumference and the bottom end face machining on a sawing machine for sawing, removing the riser on the top of the ingot, and the length of sawing off is 1 / 5 of the total height of the ingot;

[0070] (3) placing the ingot after the treatment in step (2) in a box furnace at 870° C. for 3 h to perform homogenization treatment, then taking the ingot after the homogenization treatment out of the box furnace for hot forging, the forging is completed within 2 min, and the forging deformation is 65% (the forging deformation is calculated based on the cross-sectional ratio before and after forging);

[0071] Then, the forged ingot is placed in a gas-protected tubular furnace at a temperature of 970°C (the gas in the gas-protected tubular furnace is a mixture of nitrogen and argon at a volume ratio of 1:1) and kept warm for 2 hours, then taken out and quickly placed in running tap water for cooling to complete the solution treatment. The total time for taking the ingot out of the gas-protected tubular furnace and placing it in running tap water is controlled to be no more than 5 seconds;

[0072] Then, the solution treated ingot is subjected to equal-channel angular extrusion. The process conditions of the equal-channel angular extrusion are as follows: Bc path is adopted, the extrusion speed is 10 mm / s, the number of extrusion passes is 4, the extrusion temperature is room temperature, the inner angle of the equal-channel angular extrusion channel is 90°, and the outer angle is 20°;

[0073] The ingot after equal-diameter angular extrusion is then placed in a gas-shielded tubular furnace at a temperature of 510°C (the gas in the gas-shielded tubular furnace is a mixture of nitrogen and argon in a volume ratio of 1:1) and kept warm for 10 hours. It is then taken out and cooled in the air to room temperature to complete the aging treatment to obtain a copper-chromium-scandium alloy.

[0074] Example 6

[0075] The preparation method of the copper-chromium-scandium alloy of this embodiment is the preparation method of the copper-chromium-scandium alloy of embodiment 3, and specifically comprises the following steps:

[0076] (1) Cutting, drying and surface degreasing the electrolytic copper plate and Cu-25Cr master alloy with a purity of ≥99.99%, and then adding the treated electrolytic copper plate, Cu-25Cr master alloy and pure scandium powder (Sc≥99.8%) into a smelting furnace according to a proportion for melting, the melting temperature is 1150° C., the melting time is 30 min, during the heating and melting process, the molten liquid surface is ensured to be completely covered by charcoal, and most of the air is isolated by the charcoal covering layer to achieve the melting process in a slightly oxidizing atmosphere, stirring with a graphite stirring rod and slag removal with a slag removal rod during the melting process; after the molten liquid surface becomes mirror-like, standing for 1 min, then heating the molten liquid to 1200° C., pouring the molten liquid at a temperature of 1200° C. into a metal casting mold, cooling to room temperature, and taking it out to obtain an ingot;

[0077] (2) The ingot is machined on a common lathe with a circumference and bottom end surface machining amount of 2 mm on a single side and a end surface machining amount of 2 mm; then, the ingot after circumference and bottom end surface machining is placed on a sawing machine for sawing, and the riser on the top of the ingot is removed, and the length of the sawing off is 1 / 5 of the total height of the ingot;

[0078] (3) placing the ingot after the treatment in step (2) in a box furnace at 900° C. for 3 h to perform homogenization treatment, then taking the ingot after the homogenization treatment out of the box furnace for hot forging, the forging is completed within 2 min, and the forging deformation is 60% (the forging deformation is calculated based on the cross-sectional ratio before and after forging);

[0079] Then, the forged ingot is placed in a gas-protected tubular furnace at a temperature of 950°C (the gas in the gas-protected tubular furnace is a mixture of nitrogen and argon with a volume ratio of 1:1) and kept warm for 1 hour, then taken out and quickly placed in running tap water for cooling to complete the solution treatment. The total time of taking the ingot out of the gas-protected tubular furnace and placing it in running tap water is controlled to be no more than 5 seconds;

[0080] Then, the solution treated ingot is subjected to equal-channel angular extrusion. The process conditions of the equal-channel angular extrusion are as follows: Bc path is adopted, the extrusion speed is 2 mm / s, the number of extrusion passes is 4, the extrusion temperature is room temperature, the inner angle of the equal-channel angular extrusion channel is 90°, and the outer angle is 20°;

[0081] The ingot after equal-diameter angular extrusion is then placed in a gas-shielded tubular furnace at a temperature of 480°C (the gas in the gas-shielded tubular furnace is a mixture of nitrogen and argon in a volume ratio of 1:1) and kept warm for 1 hour. It is then taken out and cooled in the air to room temperature to complete the aging treatment to obtain a copper-chromium-scandium alloy.

[0082] Experimental Example 1

[0083] In order to evaluate the mechanical properties, thermal and electrical conductivity of the copper-based alloys of Examples 1-3 and Comparative Examples 1-6, the room temperature tensile strength, elongation, electrical conductivity and thermal conductivity of the copper-based alloys of Examples 1-3 and Comparative Examples 1-6 were tested respectively, and the test results are shown in Table 1. The tensile strength test method was carried out in accordance with the provisions of the standard "GB / T228.2-2015 Tensile Test of Metallic Materials"; the elongation test method was carried out in accordance with the provisions of the standard "GB / T228.2-2015 Tensile Test of Metallic Materials"; the electrical conductivity test method was carried out in accordance with the provisions of the standard GB / T 32791-2016; and the thermal conductivity test method was carried out in accordance with the provisions of the standard ASTM E1461.

[0084] Table 1 Room temperature tensile strength, elongation, electrical conductivity and thermal conductivity of the copper-based alloys of Examples 1-3 and Comparative Examples 1-6

[0085] Copper-based alloys Tensile strength(MPa) Elongation(%) Electrical conductivity (IACS) <![CDATA[Thermal conductivity (W·(m·K) -1 )]]> Example 1 470.2 11.1 87.6% 393.8 Example 2 500.8 10.0 85.1% 393.1 Example 3 541.6 9.4 82.5% 392.5 Comparative Example 1 445.5 12.0 88.1% 394.1 Comparative Example 2 430.8 13.2 89.2% 395.7 Comparative Example 3 542.8 8.2 80.3% 378.6 Comparative Example 4 545.5 7.6 79.1% 375.3 Comparative Example 5 513.2 7.0 78.5% 373.6 Comparative Example 6 510.9 6.9 77.3% 369.5

[0086] Experimental Example 2

[0087] In order to evaluate the composition volatility of the copper-based alloys of Examples 1-3 and Comparative Examples 1-6, the experiment was repeated according to the preparation methods of the copper-based alloys of Examples 1-3 and Comparative Examples 1-6, and the number of repetitions was 3 times (for the same copper-based alloy, the difference percentage of the mass of the same raw material used in the 3 repeated experiments was not greater than 0.002%, so as to reduce the composition fluctuation caused by the instability of the raw material addition amount), and then the composition change rate of the copper-based alloys prepared in each batch was tested. The test results showed that the composition fluctuation rate of the copper-based alloys of Examples 1-3 was within ±0.02%. The maximum absolute value of the composition fluctuation rate of the copper-based alloys of Comparative Examples 1-6 reached 0.05%. In this experimental example, the composition fluctuation rate of the copper-based alloy refers to the percentage difference in the mass fraction of the same element in three copper-based alloy samples prepared in a certain embodiment or comparative example. For example, taking the three copper-based alloy samples prepared in Example 1 as an example, the mass fractions of the copper element in the three samples are A, B, and C, respectively. The fluctuation rate of the copper element in the copper-based alloy of Example 1 is (AB) / A×100, (AC) / A×100, and (BC) / B×100. Then, the fluctuation rate of the chromium element and the fluctuation rate of the scandium element in the copper-based alloy of Example 1 are calculated. The fluctuation rate of the copper element, the fluctuation rate of the chromium element, and the fluctuation rate of the scandium element in the copper-based alloy of Example 1 are collectively referred to as the composition fluctuation rate of the copper-based alloy of Example 1. It can be seen from the composition fluctuation test results of the copper-based alloys of Examples 1-3 and Comparative Examples 1-6 that the composition fluctuation rate of the copper-based alloy of Example 1-3 is smaller, indicating that the composition of the copper-based alloy of Example 1-3 is more stable and conducive to large-scale production.

Claims

1. A copper-chromium-scandium alloy, characterized in that: The copper-chromium-scandium alloy is composed of the following elements in percentage by mass: 0.16-0.2% chromium, 0.08-0.15% scandium, and the remainder is copper and inevitable impurity elements. The preparation method of the copper-chromium-scandium alloy comprises the following steps: smelting copper, copper-chromium master alloy and scandium, then casting to obtain an ingot, and then sequentially subjecting the ingot to homogenization treatment, forging, solution treatment, equal-diameter angular extrusion, and aging treatment to obtain the copper-chromium-scandium alloy.

2. The copper-chromium-scandium alloy according to claim 1, characterized in that: In the copper-chromium-scandium alloy, the mass percentage of the chromium element is 0.18-0.2%, and the mass percentage of the scandium element is 0.11-0.15%; in the copper-chromium-scandium alloy, the mass percentage of impurity elements is not more than 0.05%.

3. A method for preparing a copper-chromium-scandium alloy as claimed in claim 1 or 2, characterized in that: The following steps are involved: Copper, copper-chromium master alloy and scandium are smelted and then cast to obtain ingots, which are then subjected to homogenization treatment, forging, solution treatment, equal-diameter angular extrusion and aging treatment in sequence to obtain copper-chromium-scandium alloy.

4. The method for preparing the copper-chromium-scandium alloy according to claim 3, characterized in that: The copper-chromium master alloy is a Cu-25Cr master alloy; the smelting temperature is 1150-1250° C.; the smelting time is 30-50 minutes; and the smelting is carried out in a slightly oxidizing atmosphere.

5. The method for preparing the copper-chromium-scandium alloy according to claim 3, characterized in that: The casting temperature is 1200-1300°C.

6. The method for preparing the copper-chromium-scandium alloy according to claim 3, characterized in that: The homogenization treatment is to keep the ingot at 850°C to 900°C; the homogenization treatment time is not less than 3 hours.

7. The method for preparing the copper-chromium-scandium alloy according to claim 3 or 6, characterized in that: The deformation amount of the forging is 60% to 65%.

8. The method for preparing the copper-chromium-scandium alloy according to claim 3, characterized in that: The temperature of the solid solution treatment is 890-970° C., and the time is 0.5-2 hours; the solid solution treatment is carried out in a protective gas.

9. The method for preparing the copper-chromium-scandium alloy according to claim 3, characterized in that: The inner angle of the equal-channel angular extrusion channel is 90-110°, and the outer angle is 10-30°; the extrusion speed of the equal-channel angular extrusion is 2-10 mm / s; and the extrusion passes of the equal-channel angular extrusion are not less than 4 times.

10. The method for preparing the copper-chromium-scandium alloy according to claim 3, characterized in that: The temperature of the aging treatment is 450-510° C., and the time is 0.5-10 h.

Citation Information

Patent Citations

  • Copper-chromium-zirconium alloy and preparation method thereof

    CN109385555A